(untitled) (NEWTON: Networking and Information Technology, 2024)
Indonesia is a country that implements a regional self-government system, where each region is given the freedom to manage an exclusive area. This sovereignty does not only apply at the provincial and regional levels but also includes villages. Implementing "Law Number 6 of 2014 concerning Villages marks the beginning of a new era in village financial management". This law increases village income by allocating the Village Budget sourced from the State Budget (APBN). Village financial management is expected to be carried out more transparently, and accountably, and involve the population’s participation. Village financial management includes all activities consisting of planning, implementation, management, reporting, and accountability of village finances.